2018
DOI: 10.1038/s41598-018-26510-5
|View full text |Cite
|
Sign up to set email alerts
|

Pleasantness and trigeminal sensations as salient dimensions in organizing the semantic and physiological spaces of odors

Abstract: A major issue in human olfaction research is to characterize the main dimensions that organize the space of odors. The present study examines this question and shows that, beside pleasantness, trigeminal sensations, and particularly irritation, play an important role. These results were consistent along two different spaces constructed using semantic description and physiological responses to 105 odorants, smelled and described by human participants. Taken together, these findings suggest that salient trigemin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 66 publications
1
35
1
Order By: Relevance
“…One may consequently argue that the trigeminal aspect of the odorants drove the association with an energizing/relaxing dimension. It would be congruent with recent findings showing that the physiological response to odors is partially driven by the trigeminality of the odorants (Licon et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…One may consequently argue that the trigeminal aspect of the odorants drove the association with an energizing/relaxing dimension. It would be congruent with recent findings showing that the physiological response to odors is partially driven by the trigeminality of the odorants (Licon et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…These databases were from the Dravnieks study [26] (n = 45; i.e. 45 odorants not present in our original dataset could be used), the Boelens & Harding study [30] (n = 56), one set from the Keller et al study [15] (n = 118), and one set from the Licon et al study [31] (n = 19). Within each of these four novel sets, olfactory quality was coded using a continuous variable (Dravnieks: from 0 to 100; Boelens & Haring: from 0 to 9; Keller et al: from 0 to 100; Licon et al: from 0 to 100).…”
Section: Resultsmentioning
confidence: 99%
“…All analyses involved hierarchical clustering and PCA analysis of a descriptor distance matrix that was derived from the semantic vectors of the descriptors at hand. Previous work that has investigated the semantic organization of odor descriptors on the basis of perceptual data (e.g., Dravnieks 1985) have found that odor descriptors primarily are differentiated in terms of pleasantness, but also with respect to edibility (e.g., Kahn et al 2007;Zarzo 2008;Koulakov et al 2011;Licon et al 2018). Further, the distinction between source-based, abstract and evaluative descriptors is highly related to a difference in concreteness, the former descriptors being concrete and the latter abstract.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the identified dimensions corresponded either to "relative pleasantness" or to "cues of potential palatibility / nonpalatibility" (Castro et al, 2013: 13). More recently, Licon et al (2018) investigated the semantic space of odors on the basis of PCA analysis of odor-descriptor ratings. Participants rated 105 odors with respect to whether and how well they were described by 24 predefined descriptors 1 , and with regard to their perceptual dimensions in terms of pleasantness, edibility, familiarity and intensity.…”
Section: Introductionmentioning
confidence: 99%